Towards a Model for Corporate Governance for Algerian Companies - Gherbi, Sabah; M. Romi, Ismail; Sayah, Hamza (Finance and Business Economies Review, 2019)
The implementation of corporate governance has become one of the most essential drivers of economic growth and sustainability hence, present study aims at introducing the different governance models, and extracting prior researches’ testing results as well as analyzing and comparing between them to reach a suitable model that can be applied in the Algerian companies. For, the issue of governance garnered much interest from scholars as well as companies, yet it has been tremendously difficult to pin down one standard framework for the governance of all companies. Furthermore, the conducted research concludes with the necessity for a set of principles that go in accordance with the Algerian companies as well as adjusting the procedural definition to assess its efficiency in those companies.